How to incentivize tax compliance when households demand services? What works (better) and general limitations - Lilith Burgstaller; Sarah Necker (EconPol Forum, 2023)
Several countries use household tax credits to incentivize tax compliance in the provision of household services. Tax credits increase households' willingness to pay for an invoice; however, the effectiveness depends on their design. A tax credit that makes the financial benefit salient to consumers is most (cost-)effective. Governments should consider that tax credits are related to high windfall effects
Keywords: 330